Mathematical Analysis of a Transformed ODE from a PDE Multiscale Model of Hepatitis C Virus Infection - Kitagawa, Kosaku; Kuniya, Toshikazu; Nakaoka, Shinji; Asai, Yusuke; Watashi, Koichi; Iwami, Shingo (Bulletin of mathematical biology, 2019)
Mathematical modeling has revealed the quantitative dynamics during the process of viral infection and evolved into an important tool in modern virology. Coupled with analyses of clinical and experimental data, the widely used basic model of viral dynamics described by ordinary differential equations (ODEs) has been well parameterized. In recent years, age-structured models, called “multiscale model,” formulated by partial differential equations (PDEs) have also been developed and become useful tools for more detailed data analysis. However, in general, PDE models are considerably more difficult to subject to mathematical and numerical analyses. In our recently reported study, we successfully derived a mathematically identical ODE model from a PDE model, which helps to overcome the limitations of the PDE model with regard to clinical data analysis. Here, we derive the basic reproduction number from the identical ODE model and provide insight into the global stability of all possible steady states of the ODE model.